ANALISIS KEBIJAKAN DAN STRATEGI PENINGKATAN OPERASIONAL PELABUHAN PERIKANAN UNTIA MAKASSAR - Iswadi Iswadi; Danial Danial; Andi Asni (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
The purpose of this study was to analyze the level of implementation of the Untia Fishing Port policy and to analyze the strategies for improving the operations of the Untia Fishing Port. This research was conducted at the Untia fishing port, Makassar from May to July 2023. The method in this research was carried out using qualitative descriptive analysis and SWOT analysis by tracing the stakeholder nodes in determining operational policies at the Untia Fishing Port. Secondary data and primary data were collected through surveys with interview techniques and FGDs, using a Likert scale weighting analysis is an assessment of each parameter used as an analysis of operational policies at fishing ports. very important existence by fishermen. Fishermen asked for repairs to basic facilities, namely repair of breakwaters, and dredging in the pond area and harbor docks. From the employee's perception, all functional facilities or services have been running quite well and are included in the very important category, except for licensing services. For entrepreneurs, all business facilities are in the important category but expect the Untia Fishing Port to maximize their operations in carrying out port operations and marine tourism areas. It is hoped that with tourism activities, all economic activities at the Untia fishing port can increase and be profitable.